Scale matters: Risk perception, return expectations, and investment propensity under different scaling - Christoph Huber; Jürgen Huber (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
With a novel experimental design we investigate whether risk perception, return expectations, and investment propensity are influenced by the scale of the vertical axis in charts. We explore this for two presentation formats, namely return charts and price charts, where we depict low- and high-volatility assets with distinct trends. We find that varying the scale strongly affects people's risk perception, as a narrower scale of the vertical axis leads to significantly higher perceived riskiness of an asset even if the underlying volatility is the same. Furthermore, past returns predict future return expectations almost perfectly. In our setting perceived profitability was considered more important than perceived riskiness when making investment choices. Overall we show that adapting the scale of a chart makes it easier to recognize yearly return variations within a single security, but at the same time makes it harder to identify differences between dissimilar securities. This is something regulators should be aware of and take into account in the rules they set.
Keywords: D14; D18; G11; G41; 330; behavioral finance; judgment; risk perception; scaling; presentation format